PHLS overview of communicable diseases 1999. - Horby, P; Rushdy, A; Graham, C; O'Mahony, M (2001)
Every other year since 1995 the Public Health Laboratory Service has undertaken a consultation exercise to identify communicable diseases of high public health priority. The purpose of identifying disease priorities is to guide rational and transparent service planning and resource allocation. Also, the process aims to ensure a customer sensitive service. This paper presents the results of the priority setting exercise undertaken in 1999. A postal questionnaire was sent to 1130 key professionals involved in communicable disease control in the United Kingdom. Respondents were asked to assess the relative priority of 61 communicable diseases and to identify priority areas of work associated with these diseases. Five criteria were used to assess relative priority. The five criteria were; present burden of ill-health, social and economic impact, potential threat to health, health gain opportunity and public concern and confidence. For each disease, respondents were asked to score the importance of each criterion. Forty six percent of participants (518/1130) returned completed questionnaires. There was no significant difference in response rate by professional group. Based on the scores assigned to each of the five criteria, the relative priority of 61 communicable diseases has been established. The top ten diseases in descending order of priority are, HIV/AIDS, meningococcal diseases, Chlamydia trachomatis, influenza, tuberculosis, E. coli O157, Methicillin resistant Staphylococcus aureus, salmonellosis, transmissible spongiform encephalopathies and Helicobacter pylori. The opinion of a large number of health care professionals has been used to establish a priority rank for a wide range of communicable diseases. This work provides planners and policy makers with a synthesis of current professional opinion that can be used as a foundation for making decisions on service developments.